Effects of noisy workplace environments on the development of mental stress: FNIRS study - Alyan, E.A. (Institute of Advanced Scientific Research, Inc., 2020)
Workplace noises, such as realistic environmental and occupational noises, routinely take place in the work environment and have been linked with negative cognitive effects. Little is known about their impact on brain activity during mental stress. The current study aimed to investigate the effects of workplace environments, quiet and noisy, on brain activity and mental stress in the prefrontal cortex (PFC) using functional near-infrared spectroscopy (fNIRS). The results found that cortical activation level of HbO for quiet workplace was greater in the dorsolateral prefrontal cortex (DLPFC) and part of frontopolar area (FPA) compared to noisy workplace. The results also revealed a classification accuracy of about 91.07 in the discovery of noisy workplace group using support vector machine (SVM). These approaches using fNIRS together with a knowledge of the effect on human may possibly lead to improved performance by optimizing working environments. Â© 2020, Institute of Advanced Scientific Research, Inc. All rights reserved.